TYPES OF FUNGAL DISEASES OF MULBERRY (Academicia Globe: Inderscience Research, 2021)
Resolution of the President of the Republic of Uzbekistan dated March 29, 2017 No PP-2856 "On the organization and activities of the Association" Uzbekpaksanoat " and Resolution of the Cabinet of Ministers of the Republic of Uzbekistan dated August 11, 2017 No 616 "On the program of measures for further development of the silk industry in 2017-2021", as well as Resolution of the President of the Republic of Uzbekistan dated January 12, 2018 No PQ-3472 "On measures to further develop the silk industry in the country" will be the basis for increasing the efficiency of the industry, strengthening integration processes in the silk production complex and improving economic performance of farms and enterprises.